2021
DOI: 10.1080/09513590.2021.1988561
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of system-based intervention in reducing incidence of type 2 diabetes and to improve the postnatal metabolic profiles in women with gestational diabetes mellitus: a randomized controlled study

Abstract: Aim: The objective of this study was to determine the effectiveness of system-based intervention in reducing the incidence of diabetes and to improve the postnatal metabolic profiles among women with gestational diabetes mellitus (GDM). Materials and methods: For women in the intervention arm (n = 130), they received one session of individualized health education at 36 gestational weeks, a booklet of diabetes prevention, five-session of postpartum booster educational program which were conducted including 1 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Details on the different trials are shown in Table 2 . In four of the included trials, the primary outcomes were partly or exclusively related to postpartum weight change [ 24 , 25 , 27 , 28 ], in three studies incidence of T2DM [ 26 , 30 , 32 ], and three studies reported other measures of glycemic status [ 28 , 29 , 31 , 33 , 34 ]. Glucose-related outcomes were additionally included among the secondary outcomes in two of the articles [ 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details on the different trials are shown in Table 2 . In four of the included trials, the primary outcomes were partly or exclusively related to postpartum weight change [ 24 , 25 , 27 , 28 ], in three studies incidence of T2DM [ 26 , 30 , 32 ], and three studies reported other measures of glycemic status [ 28 , 29 , 31 , 33 , 34 ]. Glucose-related outcomes were additionally included among the secondary outcomes in two of the articles [ 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three of the studies found significant effect of intervention on weight outcome [ 24 , 25 , 28 ]. Neither was there any consistent, significant effect on blood pressure, lipid profiles, or development of metabolic syndrome [ 24 , 26 , 29 – 31 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal hyperglycemia accelerates intrauterine growth and increases the risk of macrosomia or the fetus being born large for gestational age (3), which may increase the risk of preeclampsia, neonatal hypoglycemia, shoulder dystocia, late stillbirth, or the need for caesarean section or neonatal intensive care (4)(5)(6). Moreover, maternal hyperglycemia can cause abnormal carbohydrate metabolism beyond the second generation (7)(8)(9). It has been shown that GDM modifies neurodevelopmental processes resulting in learning disability, attention deficit, and motor impairment in…”
Section: Introductionmentioning
confidence: 99%